Development of a polarized hyperspectral microscope for cardiac fiber orientation imaging - Zhou, Ximing (Proc SPIE Int Soc Opt Eng, 2020)
Myocardial fiber orientation is closely related to the functions of the heart. The development of imaging tools for depicting myocardial fiber orientation is important. We developed a polarized hyperspectral imaging microscope (PHSIM) for cardiac fiber orientation imaging, which is capable of polarimetric imaging and hyperspectral imaging. Polarimetric imaging is realized by the integration of two polarizers. Hyperspectral imaging is realized by snapscan Preliminary imaging experiments were implemented on an unstained paraffin embedded tissue slides of a chicken heart. We also set up a Monte Carlo simulation program based on the cylinder optical model to simulate the cardiac fiber structure of the sample and the optical setup of the PHSIM system, in which we can calculate the system output light intensity related to cardiac fiber orientation. According to the imaging and simulation results, there exists a variation of intensity of acquired images with the polar angles from the maximum to the minimum under different wavelengths, which should relate to the orientation of cardiac fibers. In addition, there is a shift of the polar angle where the maximum intensity appears when a rotation of the sample happened both in the simulation and imaging experiments. Further work is required for imaging more types of myocardial tissues at different parts and the design of a complete quantitative model to describe the relations among polar angles, wavelengths, and cardiac fiber orientations.